2000
DOI: 10.1038/sj.mp.4000812
|View full text |Cite
|
Sign up to set email alerts
|

The amygdala: vigilance and emotion

Abstract: Here we provide a review of the animal and human literature concerning the role of the amygdala in fear conditioning, considering its potential influence over autonomic and hormonal changes, motor behavior and attentional processes. A stimulus that predicts an aversive outcome will change neural transmission in the amygdala to produce the somatic, autonomic and endocrine signs of fear, as well as increased attention to that stimulus. It is now clear that the amygdala is also involved in learning about positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

117
1,887
15
20

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,598 publications
(2,066 citation statements)
references
References 274 publications
117
1,887
15
20
Order By: Relevance
“…On the other hand, impaired synaptic gating by PFC at the accumbens level allows greater access to conditioned amygdala reactions and the anxiety (or aggression) described in some ADHD children. Davis and Whalen (2001) have comprehensively reviewed animal and human literature concerning the role of the amygdala in fear conditioning. They found that the basolateral amygdala is involved in negative and positive affect, as well as spatial and motor learning.…”
Section: Synaptic Gating and Adhdmentioning
confidence: 99%
“…On the other hand, impaired synaptic gating by PFC at the accumbens level allows greater access to conditioned amygdala reactions and the anxiety (or aggression) described in some ADHD children. Davis and Whalen (2001) have comprehensively reviewed animal and human literature concerning the role of the amygdala in fear conditioning. They found that the basolateral amygdala is involved in negative and positive affect, as well as spatial and motor learning.…”
Section: Synaptic Gating and Adhdmentioning
confidence: 99%
“…The BLA receives information from multiple brain systems and is a site of integration with cortical territories, including those that regulate socioemotional functions [Bzdok et al, 2013; Ghashghaei and Barbas, 2002; LeDoux, 2007; Pessoa, 2011; Sah et al, 2003]. It contributes greatly to the perception, evaluation, and memory formation of emotionally salient events [Davis and Whalen, 2001; LeDoux, 2007; Moul et al, 2012]. The CMA, in contrast, is less heavily integrated with cortical circuits, though its thalamic and insular connections do allow for cortical crosstalks that seemingly shape early information processing [Bienkowski and Rinaman, 2013; Bzdok et al, 2013; Ghashghaei and Barbas, 2002; Keifer et al, 2015; Pessoa, 2011; Sah et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The CMA, in contrast, is less heavily integrated with cortical circuits, though its thalamic and insular connections do allow for cortical crosstalks that seemingly shape early information processing [Bienkowski and Rinaman, 2013; Bzdok et al, 2013; Ghashghaei and Barbas, 2002; Keifer et al, 2015; Pessoa, 2011; Sah et al, 2003]. It is the primary output site of the amygdala, and orchestrates behavioral and physiological aspects of emotion processing and associative learning via its projections to the brainstem, cerebellum, and hypothalamus [Davis and Whalen, 2001; LeDoux, 2007; Moul et al, 2012]. Noteworthy, recent theories ascribe some of the cognitive and affective deficits in psychopathy to chronic BLA hypoactivity and exaggerated CMA function, which may speculatively be reflected in BLA and CMA functional connectivity [Moul et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala is a medial temporal lobe structure that is important in identifying and interpreting cues that are associated with threatening stimuli (Davis and Whalen, 2001;Amaral, 2002;LeDoux, 2003). Considerable evidence implicates the amygdala in conditioned and unconditioned fear responses (Blanchard and Blanchard, 1972;LeDoux, 2000;Davis and Whalen, 2001;Amaral, 2003;Kalin et al, 2004), and human functional imaging studies have demonstrated increased amygdala activation in some patients with anxiety and depressive disorders (Drevets, 2003;Rauch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence implicates the amygdala in conditioned and unconditioned fear responses (Blanchard and Blanchard, 1972;LeDoux, 2000;Davis and Whalen, 2001;Amaral, 2003;Kalin et al, 2004), and human functional imaging studies have demonstrated increased amygdala activation in some patients with anxiety and depressive disorders (Drevets, 2003;Rauch et al, 2003). Furthermore, evidence supports a role for the amygdala CRF system in mediating anxiety and fear.…”
Section: Introductionmentioning
confidence: 99%